The impact of human resource management strategy on human resource outsourcing - Hasliza Abdul Halim,; Norbani Che Ha, (Penerbit Universiti Kebangsaan Malaysia, 2010)
This study examines the extent to which different types of HRM strategy influence HR outsourcing. Six types of HRM strategy, namely: expansion, cost efficiency, quality conscious, commitment, conventional and employee development were employed to test their influence on HR outsourcing. The data was gathered from a survey questionnaire of 232 manufacturing organisations of which 113 organisations engaged with HR outsourcing. The findings suggest that organisations rely on outsourcing of training, recruitment, payroll and HRIS functions when they espouse expansion HRM strategy. Quality conscious HRM strategies are significantly related to the outsourcing of payroll and HRIS functions. In addition, cost efficiency is significantly related to outsourcing recruitment but in opposite direction. Commitment HRM strategy is significantly related to the outsourcing of training and payroll functions while conventional HRM strategy is associated only to outsourcing training functions. However, employee development HRM strategy is not related to any outsourcing activities